Analisis Perbedaan Asupan Makro dan Mikro Nutrisi Sarapan terhadap Makan Siang Mahasiswa Poltekkes Aceh 2024 - Dharina Baharuddin; Abiyyu Bayu Satria; Maidar Maidar (Yayasan Literasi Sains Indonesia, 2026)
Breakfast plays an important role in supporting students’ daily activities as it serves as the primary source of energy for both the body and brain. A carbohydrate-rich breakfast can help maintain blood glucose levels, improve concentration, and enhance focus and productivity during learning activities. In contrast, skipping breakfast may lead to decreased energy, impaired concentration, and fatigue, which can negatively affect academic performance. This study aimed to analyze differences in total breakfast macronutrient and micronutrient intake and their effects on lunch consumption among students at Aceh Health Polytechnic. A true experimental approach with a Cluster Randomized Controlled Trial (CRCT) design was employed involving 32 students selected through universal sampling. Data were collected using questionnaires from August 30 to September 12, 2024, and analyzed using paired t-test, One-Way ANOVA, and non-parametric alternatives when assumptions were not met, using STATA software. The results showed no significant differences in any of the variables examined among the 6373 group, the 7383 group, and the control group (p > 0.05). Although differences in mean nutrient intake were observed, these differences were not statistically significant, while fat intake showed a tendency toward significance (p = 0.098). The intervention did not significantly affect either macronutrient or micronutrient intake. Future studies are recommended to involve larger sample sizes, longer intervention periods, and improved dietary intake monitoring to obtain more accurate results.